Feasibility of Booklet on the Utilization of Plants as Food Additives by the Montasik Community as a Reference for the Nutrition and Health Course - Eriawati Eri; Nurdin Amin; Nafisah Hanim; Ita Kausari (Barkah Publishing, 2025)
Food additives are substances intentionally added to food to influence its properties and characteristics. These additives include food colorings and flavorings. Natural colorings are derived from plants that have the potential to produce color. The Nutrition and Health course discusses food sources and nutrients (nutritional substances) and their functions for health. The obstacle faced by students in the Nutrition and Health course is related to learning about the use of plants as food additives, specifically the need for additional reference material on natural additives. This research aims to analyze the feasibility test results of a booklet based on the research